(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2020)
This article has no abstract. The first 100 words appear below: A 37-year-old man hailing from Comilla, Bangladesh (about 100 km from the capital, Dhaka, Bangladesh) got admitted himself into out department on 18th February 2020 with the complaints of abdominal distention for 9 months and shortness of breathing for 7 months. The abdominal distension was sudden in onset, progressive in nature, but there was no history of jaundice, oliguria, any heart disease, or abdominal pain. About 7 months ago, the patient experienced shortness of breathing, which was sudden in onset, gradually progressive, and occurring in mild exertion. It was so severe that the patient was unable to perform his day to day activities.